Identifying the Competency Mix Required for the Romanian IT Labor Market - Cristian GEORGESCU (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2017)
We are using data mining processes for this analysis with the aim of identifying the competency mix that offers the most chances for successfully getting hired within the target market. This analysis has been based on an association algorithm, similar to those used for shopping carts. This analysis leads us to a better allocation of our training efforts and generates a more accurate competency development plan.